Power, political economy, and historical landscapes of the modern world interdisciplinary perspectives - DeCorse, Christopher R. (Fernand Braudel Center Studies in historical social science, 2019)
"This interdisciplinary volume brings together a richly substantive collection of case studies that examine European-indigene interactions, economic relations, and their materialities in the formation of the modern world. Research has well demonstrated the extent and complexity of the varied local economic and political systems, and diverse social formations that pre-dated European contact. These preexisting systems articulated with the expanding European economy and, in doing so, shaped its emergence. Moving beyond the confines of national or Atlantic histories to examine regional systems and their historical trajectories on a global scale, the studies within this volume draw examples from the Caribbean, Mesoamerica, North America, South America, Africa, and South Asia. While the contributions are rooted in substantive studies from different world areas, their overarching aim is to negotiate between global and local frames, revealing how the expanding world-system entangled the non-Western world in global economies, yet did so in ways that were locally articulated, varied and, often, non-European in their expression"--